1989
DOI: 10.1128/aem.55.6.1406-1413.1989
|View full text |Cite
|
Sign up to set email alerts
|

Volatilization of Selenium by Alternaria alternata

Abstract: Hills evaporation pond facilities contained between 0.005 and 5 mg of Se per liter. The objective of this study was to isolate Se-methylating organisms in evaporation pond water and to assess, through enrichment and manipulation of their optimal growth parameters, the environmental factors which govern microbial Se methylation. Alternaria alternata was isolated as an active Se-methylating organism. The volatile product was identified as dimethylselenide. The effects of pH, temperature, Se substrates, and methy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

1990
1990
2008
2008

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 96 publications
(42 citation statements)
references
References 24 publications
1
41
0
Order By: Relevance
“…Of the amino acids tested, L-methionine (0.02 g C L −1 ) was found to be the most effective stimulant of DMSe evolution from pond water [47]. The proteins, egg albumen, casein, and gluten (2 g C L −1 ) substantially increased Se biomethylation causing a 23, 41, and 10% Se loss from the inventory, respectively, after 43 d of incubation [47]. It was also observed that Se biomethylation is protein-peptide-limited rather than nitrogen-, amino acid-or carbon-limited [48].…”
Section: Volatilization Of Se From Watermentioning
confidence: 97%
See 3 more Smart Citations
“…Of the amino acids tested, L-methionine (0.02 g C L −1 ) was found to be the most effective stimulant of DMSe evolution from pond water [47]. The proteins, egg albumen, casein, and gluten (2 g C L −1 ) substantially increased Se biomethylation causing a 23, 41, and 10% Se loss from the inventory, respectively, after 43 d of incubation [47]. It was also observed that Se biomethylation is protein-peptide-limited rather than nitrogen-, amino acid-or carbon-limited [48].…”
Section: Volatilization Of Se From Watermentioning
confidence: 97%
“…Increasing the temperature to 35 • C and the addition of 1% (wt/wt) glucose with a fungal inoculum, Alternaria alternata, doubled DMSe production over the controls after 25 d of incubation. Of the amino acids tested, L-methionine (0.02 g C L −1 ) was found to be the most effective stimulant of DMSe evolution from pond water [47]. The proteins, egg albumen, casein, and gluten (2 g C L −1 ) substantially increased Se biomethylation causing a 23, 41, and 10% Se loss from the inventory, respectively, after 43 d of incubation [47].…”
Section: Volatilization Of Se From Watermentioning
confidence: 98%
See 2 more Smart Citations
“…The instrument used was a Varian (Mulgrave, Victoria, Australia) SpectrAA-10 used in conjunction with a Varian vapor generation accessory (VGA-76). Operating conditions are described elsewhere [11]. This instrument has a limit of detection (LOD) of 0.06 M. With hydride generation, samples must be prepared for analysis in 6 N HCl.…”
Section: Analytical Proceduresmentioning
confidence: 99%